Animal toxins, pharmacological opportunities against brain ischemia? (REVISTA SAYWA, 2022)
Cerebrovascular diseases (CVD) comprise a group of disorders of the cerebral vasculature that decrease blood flow in the brain with temporary or permanent, generalized or focal involvement, with no apparent cause other than vascular origin. This review addresses a type of cerebrovascular accident - ischemic (CVA) - which is defined as the death of an area of ​​brain tissue as a consequence of an insufficient supply of blood and oxygen to the brain due to a blocked artery. Stroke is one of the main causes of death from chronic diseases around the world, and the second cause of death in Colombia (1). The objective is to present how peptide toxins of arachnid origin, specifically from the Phoneutria boliviensis species, could represent an alternative treatment thanks to their interesting potential in pharmacological development, since it is known that animal toxins act on specific receptors in the nervous system (SN).